Citra Pengungsi dan Masalah Sosial dalam film Capernaum Karya Nadine Labaki - Zahirah Karamatullah; Bastian Zulyeno (STISIP Widyapuri Mandiri Sukabumi, 2023)
This research will discuss a film directed by Nadine Labaki, entitled Capernaum, because it managed to touch the emotions of the audience. This film received a standing ovation for fifteen minutes at the Cannes Film Festival in May 2018 in France. The film Capernaum is one of the films that has caught the attention of the writer because it depicts the reality of the lives of refugees in Lebanon which are packaged from the perspective of children. This study uses a descriptive-analysis method with an objective approach. In this research, the writer used Burhan Nurgiyantoro's fiction assessment theory. Starting from describing the intrinsic elements including the theme, setting, plot, characters, and morals. Intrinsic elements will be applied in analyzing the social criticism contained in the film Capernaum. The purpose of this research is to know the intrinsic elements and to analyze the social criticism contained in Capernaum's film. As a result, there is social criticism to be conveyed regarding the government, family and society in the film Capernaum.